Kajian Yuridis Kejahatan Lintas Negara Berkaitan Dengan Perlindungan Data Pribadi - Yunani, Farhan A; Ilmih, Andi Aina (Media Hukum Indonesia (MHI), 2024)
The rapid development of the internet, marked by the emergence of search sites and social media such as Google, Facebook, YouTube, TikTok, Instagram, Twitter, and many more, has brought revolutionary changes in the way we interact, work, and live daily. However, while this technology provides great benefits, there are also negative impacts that need to be considered. With the rapid development of technology, cyberspace has become an arena for various forms of crime known as cybercrime. These crimes, which violate the law and harm society, are a serious threat that must be confronted and eradicated. The rapid development of technology has opened the door to various technological crimes. An unrestricted internet allows access to various sites, which criminals can exploit to violate data security and carry out manipulation. Data confidentiality is key in this digital era. Unlimited use of the internet opens up opportunities for criminals to hack systems and manipulate data. Therefore, maintaining data and report security is very important. To fight the threat of cybercrime, countries need to use effective tools, one of which is Cyber Law.